2022
DOI: 10.1111/ajt.17057
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation from controlled donation after circulatory death using simultaneous abdominal normothermic regional perfusion: A single center experience

Abstract: Lung transplantation (LT) is an established therapy for endstage lung disease in selected patients. However, the shortage of organ donors has led investigators to search for new ways to increase the donor pool, such as the use of extended-criteria donors, donation after circulatory death (DCD), or ex situ lung perfusion. 1Lung transplantation using controlled DCD (cDCD) grafts has been widely accepted worldwide, and outcomes are equivalent to those obtained with donation after brain death (DBD) donors. Over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
0
23
1
Order By: Relevance
“…However, NRP is increasingly used in DCD heart and abdominal organ procurements in the United States and has shown favorable utilization and graft outcomes for both kidney and liver transplantations compared with static cold storage 13,41,42 . NRP was also found to be safe for DCD lung retrieval in a large institutional series 43 . While no studies have demonstrated the superiority of NRP over EVP for DCD heart transplantation, this procurement strategy for DCD hearts is associated with improved utilization and posttransplant outcomes for concomitantly procured abdominal organs 44 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, NRP is increasingly used in DCD heart and abdominal organ procurements in the United States and has shown favorable utilization and graft outcomes for both kidney and liver transplantations compared with static cold storage 13,41,42 . NRP was also found to be safe for DCD lung retrieval in a large institutional series 43 . While no studies have demonstrated the superiority of NRP over EVP for DCD heart transplantation, this procurement strategy for DCD hearts is associated with improved utilization and posttransplant outcomes for concomitantly procured abdominal organs 44 .…”
Section: Discussionmentioning
confidence: 94%
“…13,41,42 NRP was also found to be safe for DCD lung retrieval in a large institutional series. 43 While no studies have demonstrated the superiority of NRP over EVP for DCD heart transplantation, this procurement strategy for DCD hearts is associated with improved utilization and posttransplant outcomes for concomitantly procured abdominal organs. 44 Despite this, the current analysis reports that NRP is currently used in a minority of DCD transplants, and our findings do not account for any potential benefit of NRP on posttransplant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a theoretical risk of compromise to organs exists because of the temperature differential between thoracic and abdominal cavities. A retrospective study of lungs transplanted from controlled DCD donors utilizing A-NRP compared with standard DBD donors demonstrated higher rates of PGD in the A-NRP DCD group (though similar PGD rate to lungs recovered from a non-NRP standard DCD donor); short-term and long-term survival was equivalent between A-NRP DCD and DBD groups [52 ▪ ]. Thoracoabdominal-NRP differs from A-NRP in that cerebral vessels are ligated to prevent blood flow to the brain while perfusion to thoracic organs is maintained.…”
Section: Normothermic Regional Perfusionmentioning
confidence: 99%
“…There was no difference in survival at 3 months, 1, and 5 years. Lung allografts from A-NRP donors did have a higher rate of PGD at 72 h, 10 vs. 3.4% [25] They point out what they consider to be flaws in view of the ACP; that reperfusion with NRP is not therapeutic, and that there is no intent to resuscitate a dead individual whom does not wish to be resuscitated [33 && ]. Instead, perfusion of only their organs occurs to honor their wishes to donate.…”
Section: Key Pointsmentioning
confidence: 99%